Rosemary Statelova, Angela Rodel, Lozanka Peycheva, Ivanka Vlaeva and Venstislav Dimov (eds.): The Human World and Musical Diversity. Proceedings from the Fourth Meeting of the “Music and Minorities” Study Group in Varna, Bulgaria, 2006.: Sofia: Institute of Art Studies 2008. 407 p. + 1 CD. - Jurková, Zuzana (Lidé města, 2008)
A review of the book by Rosemary Statelova, Angela Rodel, Lozanka Peycheva, Ivanka Vlaeva and Venstislav Dimov.